Vaginal Cleansing Before Cesarean Delivery: A Systematic Review and Meta-analysis. Issue 3 (September 2017) - Caissutti, Claudia; Saccone, Gabriele; Zullo, Fabrizio; Quist-Nelson, Johanna; Felder, Laura; Ciardulli, Andrea; Berghella, Vincenzo
Abstract : OBJECTIVE: To assess the efficacy of vaginal cleansing before cesarean delivery in reducing postoperative endometritis. DATA SOURCES: MEDLINE, Ovid, EMBASE, Scopus, Clinicaltrials.gov, and Cochrane Library were searched from their inception to January 2017. METHODS OF STUDY SELECTION: Selection criteria included all randomized controlled trials comparing vaginal cleansing (ie, intervention group) with a control group (ie, either placebo or no intervention) in women undergoing cesarean delivery. Any method of vaginal cleansing with any type of antiseptic solution was included. The primary outcome was the incidence of endometritis. Meta-analysis was performed using the random-effects model of DerSimonian and Laird to produce summary treatment effects in terms of relative risk (RR) with 95% CI. TABULATION, INTEGRATION, AND RESULTS: Sixteen trials (4, 837 women) on vaginal cleansing immediately before cesarean delivery were identified as relevant and included in the review. In most of the included studies, 10% povidone–iodine was used as an intervention. The most common way to perform the vaginal cleansing was the use of a sponge stick for approximately 30 seconds. Women who received vaginal cleansing before cesarean delivery had a significantly lower incidence of endometritis (4.5% compared with 8.8%; RR 0.52, 95% CI 0.37–0.72; 15 studies, 4, 726 participants) and of postoperative fever (9.4% compared with 14.9%; RR 0.65, 95% CI 0.50–0.86; 11 studies, 4, 098 participants) compared with the control group. In the planned subgroup analyses, the reduction in the incidence of endometritis with vaginal cleansing was limited to women in labor before cesarean delivery (8.1% compared with 13.8%; RR 0.52, 95% CI 0.28–0.97; four studies, 440 participants) or those with ruptured membranes (4.3% compared with 20.1%; RR 0.23, 95% CI 0.10–0.52; three studies, 272 participants). CONCLUSION: Vaginal cleansing immediately before cesarean delivery in women in labor and in women with ruptured membranes reduces the risk of postoperative endometritis. Because it is generally inexpensive and a simple intervention, we recommend preoperative vaginal preparation before cesarean delivery in these women with sponge stick preparation of povidone–iodine 10% for at least 30 seconds. More data are needed to assess whether this intervention may be also useful for cesarean deliveries performed in women not in labor and for those without ruptured membranes. SYSTEMATIC REVIEW REGISTRATION: PROSPERO International prospective register of systematic reviews, https://www.crd.york.ac.uk/PROSPERO/, CRD42017054843. Abstract : Vaginal cleansing immediately before cesarean delivery reduces the risk of postoperative endometritis in women who have labored or who have ruptured membranes.